Program Coaching: Pembelajaran Aplikasi RedSeller sebagai Penunjang Promosi Media Sosial di RedDoorz Indonesia - Rossa, Eva Yulia; Swasti, Ika Korika (Universitas Pahlawan Tuanku Tambusai, 2026)
The development of digital marketing is encouraging service companies, including the hospitality sector, to develop digital reseller-based marketing models. RedDoorz implemented a coaching program through the RedSeller app as part of its training program for new resellers. This community service program aimed to evaluate the effectiveness of the RedSeller coaching program in improving new resellers' understanding of app usage and digital marketing readiness. The method used was descriptive qualitative through participatory observation, pre- and post-tests in the form of open-ended questions, and documentation of coaching activities and follow-up mentoring. The program was conducted online via Google Meet and supported by mentoring through a WhatsApp group. The results showed an increase in RedSellers' understanding of RedSeller app features and digital promotion strategies after participating in the coaching. However, a single coaching session is not entirely sufficient, requiring ongoing mentoring. Therefore, it is recommended to strengthen coaching materials, provide video tutorials, promotional content templates, and provide regular thematic webinars.